Echocardiography does not predict mortality in hemodynamically stable elderly patients with acute pulmonary embolism. Issue 145 (September 2016) - Hofmann, Eveline; Limacher, Andreas; Méan, Marie; Kucher, Nils; Righini, Marc; Frauchiger, Beat; Beer, Jürg-Hans; Osterwalder, Joseph; Aschwanden, Markus; Matter, Christian M.; Banyai, Martin; Egloff, Michael; et al.
Abstract: Background: The evidence on the prognostic value of transthoracic echocardiography (TTE) in elderly, hemodynamically stable patients with Pulmonary Embolism (PE) is limited. Objectives: To evaluate the prevalence of common echocardiographic signs of right ventricular (RV) dysfunction and their prognostic impact in hemodynamically stable patients aged ≥ 65 years with acute PE in a prospective multicenter cohort. Methods: TTE was performed by cardiologists. We defined RV dysfunction as a RV/left ventricular ratio > 0.9 or RV hypokinesis (primary definition) or the presence of ≥ 1 or ≥ 2 of 6 predefined echocardiographic signs (secondary definitions). Outcomes were overall mortality and mortality/non-fatal recurrent venous thromboembolism (VTE) at 30 days, adjusting for the Pulmonary Embolism Severity Index risk score and highly sensitive troponin T values. Results: Of 400 patients, 36% had RV dysfunction based on our primary definition, and 81% (≥ 1 sign) and 53% (≥ 2 signs) based on our secondary definitions, respectively. Using our primary definition, there was no association between RV dysfunction and mortality (adjusted HR 0.90, 95% CI 0.31–2.58) and mortality/non-fatal VTE (adjusted HR 1.09, 95% CI 0.40–2.98). Similarly, there was no statistically significant association between the presence of ≥ 1 or ≥ 2 echocardiographic signs (secondary definitions) and clinical outcomes. Conclusion: The prevalence of echocardiographic RV dysfunction varied widely depending upon the definition used. There was no association between RV dysfunction and clinical outcomes. Thus, TTE may not be suitable as a stand-alone risk assessment tool in elderly patients with acute PE. Clinical trial registration: http://clinicaltrials.gov . Identifier:NCT00973596 . Highlights: In the elderly stable patient with acute PE the prevalence of RV dysfunction on TTE varies based on the definition used. No association between right ventricular dysfunction and short-term clinical outcomes. TTE as a stand-alone risk stratification tool in the elderly with acute PE is not recommended.